2012
DOI: 10.1039/c2ce25117e
|View full text |Cite
|
Sign up to set email alerts
|

Sr-fresnoite surface crystallisation in a 2SrO·TiO2·2.75 SiO2 glass studied by EBSD

Abstract: A glass of the composition 2SrO?TiO 2 ?2.75SiO 2 was melted. Cooled samples were polished and thermally annealed at 970 uC for 10 min to 20 h to achieve surface crystallisation of Sr 2 TiSi 2 O 8 fresnoite. At the surface, the crystals were immediately oriented with their crystallographic c-axes perpendicular to the surface. Crystal growth occurred in the form of similarly oriented structures. Very homogeneous structures were also observed but they fray into areas of higher orientation diversity at some distan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
95
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(111 citation statements)
references
References 32 publications
16
95
0
Order By: Relevance
“…The lack of bulk crystallization allowed us to conclude that nucleation occurred solely on the surfaces. This seems to be in contradiction to the crystallization of BTS reported in [19], but comparable with data shown by W. Wisniewski for the surface crystallization of Sr 2 TiSi 2 O 8 fresnoite [39][40][41]. The EDX spectra of samples support the above XRD results.…”
Section: Discussionsupporting
confidence: 50%
“…The lack of bulk crystallization allowed us to conclude that nucleation occurred solely on the surfaces. This seems to be in contradiction to the crystallization of BTS reported in [19], but comparable with data shown by W. Wisniewski for the surface crystallization of Sr 2 TiSi 2 O 8 fresnoite [39][40][41]. The EDX spectra of samples support the above XRD results.…”
Section: Discussionsupporting
confidence: 50%
“…also observed in STS containing glass-ceramics3839. Polarization micrographs of cross sections have been published24 and indicate a strong optical anisotropy.…”
mentioning
confidence: 92%
“…Samples annealed at only 695 and 700 °C have been proposed to show XRD-patterns similar to the powder pattern16 and it was concluded that the crystalline phase is not oriented at the surface161724. 001 textures have also been indicated by XRD in BTS4041 and STS38 glass-ceramics, but the application of EBSD showed that the topmost layer shows a different orientation in the case of BTS40 which is affected by the annealing temperature40. Actually, the analysis of surface crystallized STS from the composition STS+0.45 SiO 2 provided the first case where the texture detected at the immediate surface also prevailed during growth39 while a texture change is observed more often33404243.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…with piezoelectric properties in the case of fresnoite [1,2]. The main mystery of this process is the surface nucleation itself, which has recently been realized to be more complicated than previously thought as oriented nucleation has been shown to occur in a number of surface crystallizing glass systems [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 98%